(untitled) (Asian Journal of Medical and Biological Research, 2021)
Mycoplasma gallisepticum (MG) is the most important pathogenic Mycoplasma spp. causing avian mycoplasmosis and brought about huge economic losses to poultry industry in Bangladesh. The present study was undertaken to know the seroprevalence of MG in layer birds in three different geographical areas of southern Barishal division, Bangladesh. Total 310 sera samples were collected from wing vein of 30 farms for this study. Sera samples were tested with Rapid Serum Agglutination (RSA) for MG using commercial Antigen Kit (manufactured by Lillidale Diagnostic) to detect the presence of antibodies against MG. The overall seroprevalence of MG by RSA was 36.13%. Seroprevalence of MG infection was dominant in winter season (45.54%) and significantly highest occurrence was recorded in age groups from 20-40 weeks of layer chickens (51.79%). Serological investigation in three different upazila of Barishal division showed the highest infection rate (45.26%) in medium scale flocks (1000-3000) in comparison to (21.43%) small (<1000) flocks. The seroprevalence of MG was highest in Swarupkathi (44.38%) than in Barishal Sadar (26%) and Banaripara upazila (28%). Biosecurity and managemental failure is the overall risk factor in all types of farm due to lack of proper knowledge among farmer. This study reveals the current scenario of mycoplasmosis in layer birds of three different areas of Barishal division. Asian J. Med. Biol. Res. 2021, 7 (3), 292-297